1968
DOI: 10.1139/b68-035
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide compensation—its relation to photosynthetic carboxylation reactions, systematics of the Gramineae, and leaf anatomy

Abstract: The carbon dioxide compensation concentration of members of the Gramineae and a few other plants was determined with an infrared CO2 analyzer. These results were then considered in relation to the new photosynthetic carboxylation pathway proposed by Hatch et al., rates of photosynthesis, grass systematics, leaf anatomy, and distribution of starch in the leaf. Plants possessing the new carboxylation pathway had low compensation values whereas those having the Calvin carboxylation reaction had high values. Low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(81 citation statements)
references
References 24 publications
3
78
0
Order By: Relevance
“…The studies of Hatch et al (9, 10O have shown that wheat and oats form intermediates of the Calvin cycle as the earliest products of photosynthesis. These plants also have photorespiration (5). Corn and many tropical grasses, which lack photorespiration, have a different carboxylation sequence in which C-4 compounds are labeled first (5,10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of Hatch et al (9, 10O have shown that wheat and oats form intermediates of the Calvin cycle as the earliest products of photosynthesis. These plants also have photorespiration (5). Corn and many tropical grasses, which lack photorespiration, have a different carboxylation sequence in which C-4 compounds are labeled first (5,10).…”
Section: Resultsmentioning
confidence: 99%
“…These plants also have photorespiration (5). Corn and many tropical grasses, which lack photorespiration, have a different carboxylation sequence in which C-4 compounds are labeled first (5,10). This appears to be true also for low compensation members of the Amaranthaceae and Chenopodiaceae (27, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Monocots and dicots were classed as photosynthetically efficient or inefficient from published comparisons of the response of photosynthesis to 02 concentration (4,9) or of the CO, compensation concentration among species (3,5,13). Triticale, the interspecific hybrid of wheat and rye, was classed inefficient by the characteristics of its parents.…”
Section: Methodsmentioning
confidence: 99%
“…Growth of Phaseolus vulgaris, Mimulus cardinalis, and the liverwort Marchantia polymorpha increased when aerial portions of the plants were maintained in low 02 compared with ambient air (1,2). Photosynthesis in the leaves of efficient species is not enhanced by low 02 (4, 9) nor is growth stimulated (1,2); this is not surprising since these species have either no photorespiration or show quite low rates (5,14).…”
mentioning
confidence: 99%
“…
,1u CO2/l air) for species with inefficient photosynthesis and high photorespiration, and low (<10 pI CO2/l air) for species with efficient photosynthesis and negligi-ble photorespiration (4,16,25,26).Maize belongs to this latter group (14, 16), and has a rCO2L, independent of°2 concentration (15,20).Recent models demonstrate that the magnitude of the [CO2], depends upon the diffusive resistance of the leaf to CO2, the efficiency of CO2 fixation in the chloroplasts, and the respiration rate of the leaf (1,21,24).A second, lesser used, method exists for predicting the photosynthetic efficiency of leaves. The Michaelis constant (Km) of a leaf has been postulated (7) as "the external CO2 concentration which enables the leaf, at saturating light intensity, to fix CO2 at half the maximal velocity".
…”
mentioning
confidence: 98%